2009
DOI: 10.1177/002204260903900209
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of a Smoking Cessation Clinical Trial Affect Staff Practices Related to Smoking?

Abstract: This study investigated whether organizational changes occurred when nicotine treatments were tested in specialty care clinics. Two intervention clinics (one drug treatment and one HIV-care) participated in clinical trials for nicotine treatment. Three clinics (two drug and one HIV-care) were control clinics. Staff in the intervention clinics (n=57) and in the control clinics (n=62) were surveyed at baseline and 18 months later. Staff surveys concerned nicotine-related knowledge, beliefs about treating smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The five S-KAP scales, each scored from 1 to 5, reflect Knowledge of the hazards of smoking (α = 0.85), Attitudes about treating smoking in addiction programs (α = 0.74), Barriers to providing tobacco treatment (α = 0.81), counselor Self-efficacy in providing tobacco-related services (α = 0.72) and Practices used to address tobacco dependence with clients (α = 0.91) (Delucchi et al, 2009). S-KAP scales previously distinguished different levels of practices in different clinics (Tajima et al, 2009), and were used to assess change when clinics participated in smoking-cessation trials (Chun et al, 2009). Two scales are calculated for all staff (Knowledge, Attitudes), while remaining scales are calculated for clinical staff only (Barriers, Self-Efficacy, Practices).…”
Section: Methodsmentioning
confidence: 99%
“…The five S-KAP scales, each scored from 1 to 5, reflect Knowledge of the hazards of smoking (α = 0.85), Attitudes about treating smoking in addiction programs (α = 0.74), Barriers to providing tobacco treatment (α = 0.81), counselor Self-efficacy in providing tobacco-related services (α = 0.72) and Practices used to address tobacco dependence with clients (α = 0.91) (Delucchi et al, 2009). S-KAP scales previously distinguished different levels of practices in different clinics (Tajima et al, 2009), and were used to assess change when clinics participated in smoking-cessation trials (Chun et al, 2009). Two scales are calculated for all staff (Knowledge, Attitudes), while remaining scales are calculated for clinical staff only (Barriers, Self-Efficacy, Practices).…”
Section: Methodsmentioning
confidence: 99%
“…In the first study, two intervention clinics (one substance abuse treatment clinic and one HIV care clinic) participated in clinical trials for smoking cessation. Three additional clinics (two substance abuse and one HIV care) were recruited as control clinics (Chun et al, in press). All of the clinics were either VAMC substance abuse treatment clinics or hospital-based HIV care clinics.…”
Section: Methodsmentioning
confidence: 99%
“…For 8 of the 11 studies, however, post-intervention smoking quit rates were below 10%. At least two studies have now observed an approximate 10% smoking cessation rate among persons enrolled in drug treatment where no specific smoking intervention was provided (Chun, Guydish, & Delucchi, in press; Kohn, Tsoh, & Weisner, 2003). Smoking cessation interventions that achieve only a 10% rate for persons enrolled in substance abuse treatment may be reflecting only ongoing background quit attempts in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Due to concurrent pressing political, economic and social issues stemming from the break up of the former Soviet Union, the public health of PWID was not a priority (Cohen, 2010; Hurley, 2010). Since then, research has been concentrated in this region to help stem the tide of HIV transmission for PWID (Booth et al, 2010, 2009, 2006a, 2006b, 2004; Kruglov et al, 2008; Taran et al, 2011; Kyrychenko and Polonets, 2005; Booth, 2009). The HIV epidemic in Ukraine has been characterized by high rates of transmission among PWID, with other risk groups such as men who have sex with men (MSM) and female sex workers (FSWs) increasingly represented (Kruglov et al, 2008; UNAIDS 2010; Baral et al, 2012).…”
Section: Introductionmentioning
confidence: 99%